The Efficacy of Fat Grafting on Treating Post-Mastectomy Pain with and without Breast Reconstruction: A Systematic Review and Meta-Analysis - Jeffrey Chen; Abdulrahman A. Alghamdi; Chi Yi Wong; Muna F. Alnaim; Gabriel Kuper; Jing Zhang (Current Oncology, 2024)
Post-mastectomy pain syndrome (PMPS), characterized by persistent pain lasting at least three months following mastectomy, affects 20–50% of breast surgery patients, lacking effective treatment options. A review was conducted utilizing EMBASE, MEDLINE, and all evidence-based medicine reviews to evaluate the effect of fat grafting as a treatment option for PMPS from database inception to 29 April 2023 (PROSPERO ID: CRD42023422627). Nine studies and 812 patients in total were included in the review. The overall mean change in visual analog scale (VAS) was −3.6 in 285 patients following fat grafting and 0.5 in 147 control group patients. There was a significant reduction in VAS from baseline in the fat grafting group compared to the control group, n = 395, mean difference = −2.17 (95% CI, −2.95 to −1.39). This significant improvement was also noted in patients who underwent mastectomy without reconstruction. Common complications related to fat grafting include capsular contracture, seroma, hematoma, and infection. Surgeons should consider fat grafting as a treatment option for PMPS. However, future research is needed to substantiate this evidence and to identify timing, volume of fat grafting, and which patient cohort will benefit the most.